2014
DOI: 10.1074/jbc.r114.576876
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Physiological Roles for Phospholipase D1 in Cancer

Abstract: Phospholipase D enzymes have long been proposed to play multiple cell biological roles in cancer. With the generation of phospholipase D1 (PLD1)-deficient mice and the development of small molecule PLD-specific inhibitors, in vivo roles for PLD1 in cancer are now being defined, both in the tumor cells and in the tumor environment. We review here tools now used to explore in vivo roles for PLD1 in cancer and summarize recent findings regarding functions in angiogenesis and metastasis. The phospholipase D (PLD)2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 101 publications
1
34
0
1
Order By: Relevance
“…In addition to the DGKs, the lysophosphatidic acid acyltransferases (LPAATs) and phospholipase D (PLD) enzymes also generate PA. LPAAT and PLD enzymes have also been linked to cancer, further supporting roles for PA in malignant cells (2124). Though all DGKs convert DAG to PA, they may still play unique roles in cancer given their different cellular localizations.…”
Section: Introductionmentioning
confidence: 86%
“…In addition to the DGKs, the lysophosphatidic acid acyltransferases (LPAATs) and phospholipase D (PLD) enzymes also generate PA. LPAAT and PLD enzymes have also been linked to cancer, further supporting roles for PA in malignant cells (2124). Though all DGKs convert DAG to PA, they may still play unique roles in cancer given their different cellular localizations.…”
Section: Introductionmentioning
confidence: 86%
“…The combination of PLD1 and autophagy inhibition was shown to synergize in inducing tumor cell apoptosis and tumor regression, providing a potential rational target for anticancer therapy (91). In earlier studies, short-chain primary alcohols were used as PLD inhibitor, but concerns were raised about insufficient suppression of PA production and off-target effects (92). Several PLD-specific inhibitors have been screened and evaluated in preclinical studies (81, 92, 93).…”
Section: Ptdcho-specific Phospholipase D (Pld)mentioning
confidence: 99%
“…In earlier studies, short-chain primary alcohols were used as PLD inhibitor, but concerns were raised about insufficient suppression of PA production and off-target effects (92). Several PLD-specific inhibitors have been screened and evaluated in preclinical studies (81, 92, 93). 5-Fluoro-2-indolyl des-chlorohalopemide (FIPI), a dual inhibitor of PLD1 and PLD2 (93), has shown anticancer potential.…”
Section: Ptdcho-specific Phospholipase D (Pld)mentioning
confidence: 99%
“…The development of a pharmacological approach was sparked by the identification of halopemide, a neuropsychiatric drug, as a robust PLD inhibitor [29, 30]. An analog, denoted FIPI [23], is a potent inhibitor of both PLD1 and PLD2, has a half-life and bioavailability parameters that have permitted it to be used widely in cell culture and animal studies, and thus far has phenocopied outcomes observed with knockout cells and animals and with RNAi [24, 3134].…”
Section: Pld1 and Pld2 The Signaling-activated Enzymesmentioning
confidence: 99%
“…As discussed above, the vast majority of studies more than five years old relied on alcohol-mediated inhibition or other non-specific means of altering PLD activity and thus need to be interpreted with caution. These are discussed in extensive detail in recent reviews [29, 30]. However, studies using modern small molecule inhibitors, animals lacking PLD isoforms, and genetic models are starting to provide a clearer picture of potential utility for PLD inhibitors.…”
Section: Therapeutic Opportunities For Pld Inhibitionmentioning
confidence: 99%